2022
DOI: 10.1002/vms3.990
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary supplementation of coenzyme Q10 on reproductive variables of cadmium‐challenged male Japanese quails (Coturnix Japonica)

Abstract: Background:In recent decades, efforts to produce more efficient poultry products have increased due to its high demand. Meanwhile, some stressors have a negative impact on poultry efficiency and reproduction. Cadmium (Cd) is a toxic heavy metal with a high potential for inducing reactive oxygen species. On the other hand, coenzyme Q10 (CoQ10), with antioxidant properties, exerts a free radical-neutralizing effect on biological systems under stressful conditions.Objectives: This study aimed to determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…CoQ10 has been investigated in several studies for its effects on testicular damage caused by various agents, including cadmium [26], lead [27], radiation [17], and smoking [10] were investigated. However, in the literature review, no study has been found regarding the protective effect of CoQ10, administered at different time points, on the damage induced by CP application.…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…CoQ10 has been investigated in several studies for its effects on testicular damage caused by various agents, including cadmium [26], lead [27], radiation [17], and smoking [10] were investigated. However, in the literature review, no study has been found regarding the protective effect of CoQ10, administered at different time points, on the damage induced by CP application.…”
Section: Histopathological Examinationmentioning
confidence: 99%